Deal or No Deal? Decision-making under Risk in a Large-payoff Game Show - Thierry Post; Guido Baltussen; Martijn van den Assem (Tinbergen Institute, 2006)
We examine the risky choices of contestants in the popular TV game show “Deal or No Deal” and related classroom experiments. Contrary to the traditional view of expected utility theory, the choices can be explained in large part by previous outcomes experienced during the game. Risk aversion decreases after earlier expectations have been shattered by unfavorable outcomes or surpassed by favorable outcomes. Our results point to reference-dependent choice theories such as prospect theory, and suggest that path-dependence is relevant, even when the choice problems are simple and well defined, and when large real monetary amounts are at stake.
Keywords: D81; C23; C93; 330; Decision making under risk; Relative risk aversion; break-even effect; real incentives; game show; Entscheidungstheorie; Spieltheorie; Prospect Theory; Theorie